The Influence of Planting Density on Maize-Soybean Intercropping Inoculated with Organic Fertilizer - Astiko, Wahyu; Ernawati, Ni Made Laksmi; Silawibawa, I Putu (KnE Life Sciences, 2022)
Mycorrhizae and organic fertilizers play a critical role in nutrient availability and absorption, soil texture development, and hormone production to promote plant growth. The aim of this research was to determine the influence of planting density on intercropping maize and mycorrhizal soybeans, and the impact of organic fertilizers on maize and soybean yields in dry lands in North Lombok. The experiment was conducted using a randomized block design with five intercropping treatments: P1 = 2 maize lines: 2 soybean lines, P2 = 3 maize lines: 2 soybean lines, P3 = 3 maize lines: 3 soybean lines, P4 = 4 maize lines: 2 soybean lines, and P5 = 4 maize lines: 3 soybean lines. The data were then analyzed using two-way ANOVA and Tukey’s significant difference test with a significance level of 5%. It was found that the P3 density showed the highest yield compared with the other intercropping treatments; the number of spores and mycorrhizal infection rate were also increased. The P3 treatment, with the addition of 15 tons of cow manure per hectare and inoculation with AMF, enhanced the yield and promoted the development of mycorrhiza. Keywords: Intercropping; maize; plant density; soybean